(untitled) (Research, Society and Development, 2022)
Aromas bring memories that evoke emotions, which can influence food acceptance. This ability to arouse emotions can be affected by some of its characteristics such as concentration and familiarity. Thus, this work aimed to evaluate the emotional and hedonic response at two levels of aroma concentration and to understand if there was an influence of familiarity on these responses. The aromas studied were vanilla, cinnamon, basil, strawberry and tangerine, evaluated in two sessions, one with concentrated aromas and the other with diluted aromas. A check-all-that-apply (CATA) questions were designed and applied in both sessions with 76 consumers, jointly with the nine-point hedonic scale and the three-point familiarity scale. The results showed that for strawberry, vanilla and basil the dilution did not influence the hedonic and emotional response since strawberry and vanilla remained with greater acceptance and associated with positive emotions, while basil remained rejected and associated with negative emotions. In contrast, dilution had a positive effect on tangerine, as it favored its acceptance and made its emotional response closer to that of strawberry and vanilla. As for cinnamon, the dilution had a negative effect, as it made the response to this aroma similar to that of basil, decreasing its acceptance. In addition, evidence was found that low familiarity associated with low aroma concentration may impair its acceptance. Thus, it is important to consider concentration and familiarity to obtain a better performance in the affective response to aromas.